More than just a show: extending the impact of museum exhibitions for good - Salter, Kerryn Elizabeth (Nanyang Technological University, 2022)
In our world today, greater attention is paid to fostering social responsibility, sustainability, inclusiveness, diversity, multi-perspectivity, as well as achieving decolonization and the flattening of hierarchies that have enabled and maintain inequalities of power, agency, and resources. These concerns become even more pronounced in the museum context, as they are reflected and reproduced in this institution’s production of cultural knowledge. In addition to this consideration, there are also concerns that are specific to museums, such as how their collections have been acquired and associated issues of object ownership and calls for repatriation, as well as how national histories and “other” cultures have been presented (or excluded) by them. As a result, increasingly and more vociferously, there are calls for museums to be accountable, to address these systemic and institutionally embedded issues, and to be a proactive player and force for good in engaging audiences in broader social, political, economic, and ecological issues, in ways that provoke curiosity, criticality, and dialogue. Given these circumstances, to sustain their cultural importance, popularity, and ultimately their survival – while still retaining their core functions, such as collecting and safekeeping objects from the past for future posterity – museums need to attend to the contemporary and evolving social, cultural, and educational needs and interests of the diverse communities they serve. To accomplish these, museums must change and strive to be more accessible, inclusive, participatory, ethical, and sustainable on an ongoing basis; and also effectively demonstrate the authenticity and substantive nature of these efforts. I propose that one way in which this can be accomplished is by museums acknowledging and reflecting these concerns and developments to a greater degree in their core activities – in particular, via how they curate and display their exhibitions, which leverage the museum’s primary resource (i.e., its collections) and its existing competencies. As such, this dissertation focuses on how museum collections can be curated and exhibited more adaptively to the contemporary concerns noted above, and suggests strategies, by way of looking into case studies and best practices that incorporate contemporary art, artist interventions, and curatorial practices, that museum curators can consider as part of their efforts. A key factor I keep in mind during this investigation is the importance for museums to maintain their cultural relevance and ideological freedom, while also being able to survive as financially viable institutions. In this regard, I stress the need for museums to carefully consider with whom they wish to partner, and to work towards attracting like-minded sponsors who authentically share the same community-centric values they espouse.